Thrombectomy for secondary distal, medium vessel occlusions of the posterior circulation: seeking complete reperfusion. (16th July 2021) - Meyer, Lukas; Stracke, Christian Paul; Wallocha, Marta; Broocks, Gabriel; Sporns, Peter B; Piechowiak, Eike I; Kaesmacher, Johannes; Maegerlein, Christian; Dorn, Franziska; Zimmermann, Hanna; Naziri, Weis; Abdullayev, Nuran; et al.
Abstract : Background: Whether to approach distal occlusions endovascularly or not in medium-sized vessels secondary to proximal large vessel occlusion stroke remains unanswered. Objective: To investigates the technical feasibility and safety of thrombectomy for secondary posterior circulation distal, medium vessel occlusions (DMVO). Methods: TOPMOST (Treatment fOr Primary Medium vessel Occlusion STroke) is an international, retrospective, multicenter, observational registry of patients treated for distal cerebral artery occlusions. This study subanalysis endovascularly treated occlusions of the posterior cerebral artery in the P2 and P3 segment secondary preprocedural or periprocedural thrombus migration between January 2014 and June 2020. Technical feasibility was evaluated with the modified Thrombolysis in Cerebral Infarction (mTICI) scale. Procedural safety was assessed by the occurrence of symptomatic intracranial hemorrhage (sICH) and intervention-related serious adverse events. Results: Among 71 patients with secondary posterior circulation DMVO who met the inclusion criteria, occlusions were present in 80.3% (57/71) located in the P2 segment and in 19.7% (14/71) in the P3 segment. Periprocedural migration occurred in 54.9% (39/71) and preprocedural migration in 45.1% (32/71) of cases. The first reperfusion attempt led in 38% (27/71) of all cases to mTICI 3. On multivariable logistic regression analysis, increased numbers of reperfusion attempts (adjusted odds ratio (aOR)=0.39, 95% CI 0.29 to 0.88, p=0.009) and preprocedural migration (aOR=4.70, 95% CI, 1.35 to 16.35, p=0.015) were significantly associated with mTICI 3. sICH occurred in 2.8% (2/71). Conclusion: Thrombectomy for secondary posterior circulation DMVO seems to be safe and technically feasible. Even though thrombi that have migrated preprocedurally may be easier to retract, successful reperfusion can be achieved in the majority of patients with secondary DMVO of the P2 and P3 segment.